KİNDÎ METAFİZİĞİ - (:unkn) unknown (My University, 2018)
Kindî’nin günümüze ulaşan eserleri bir bütün olarakincelendiğinde onun metafizik tasavvurunun esasitibariyle üç kavram ve önermeden oluştuğu görülür.Hak kavramının tahlili, Kindî’yi her nesnenin sahipolduğu gerçekliğin nihai bir ilkesi bulunduğu ve builkenin de ilk gerçek olması gerektiği sonucuna ulaştırır.Vahdet kavramının tahlili Kindî’yi her bir nesneninsahip olduğu birliğin nihai bir ilkeye dayandığı ve bunihai ilkede ise birlik ve birin özdeş olması gerektiğisonucuna ulaştırır. Hareket kavramına ilişkin tahlilleri,Kindî’yi harekete konu olabilecek her şeyin hâdisolduğu ve bütün hâdislerin ise ezelî bir fâile dayanmasıgerektiği sonucuna ulaştırır. Bu kavram ve önermeleraynı zamanda Kindî’nin metafizik tasavvurunu daoluşturur. Ona göre metafizik, nihai gerçek, mutlak birve ezelî fâile ilişkin bilgidir.

When the works of al- Kindi that are available today are e amined as whole, it is possible to discern his understanding of metaphysics as being formed essentially of three concepts and propositions. The analysis of the concept of the truth (ha ) leads al-Kindi to the conclusion that there e ists an ultimate principle for the reality possessed by every object, and this principle must be the first reality. The e amination of the concept of unity (wahdah) takes al-Kindi to the conclusion that the unity possessed by every object is based on an ultimate principle, and at the level of this ultimate principle, unity and oneness must be identical. The analyses related to the concept of movement results in the conclusion that every thing to be subject to movement must be temporal (hadith), and all such temporally created objects must rely on an eternal agent that brings them about. These concepts and propositions simultaneously form al-Kindi’s conception of metaphysics. According to him, metaphysics is the knowledge of an agent that is eternal and absolutely one, the ultimate reality.
AL-KINDI’S METAPHYSICS
Keywords: Din Bilimi